Effect of Helicobacter pylori VacA on gene expression of gastric cancer cells - Wang, Hong-Tao (Baishideng Publishing Group Inc, 2005)
AIM: To determine the effect of Helicobacter pylori VacA on gene expression of gastric cancer cells. METHODS: Gene expression profile of a gastric cancer cell line, SGC7901, after challenged by VacA(+) and VacA(-) H pylori broth culture supernatants (BCS), was detected by the cDNA microarray technique. Cytoskeleton changes of SGC7901 and HeLa cells were observed through high-resolution laser scanning confocal microscopy. RESULTS: A total of 16000 cDNA clones were detected. The percentage of genes with heterogeneous expression in SGC7901 cells challenged by VacA(+) BCS reached 5%, compared with that challenged by VacA(-) BCS. There were 865 genes/EST with 2-fold differential expression levels and 198 genes/EST with 3-fold differential expression levels. Most of these genes were involved in vital cell events including signal transduction, regulation of gene expression, cytoskeleton, apoptosis, stress response and inflammation, cell cycle and tumor development. Cells co-cultured with VacA(+) BCS showed collapsed and disrupted microtubular cytoarchitecture. CONCLUSION: VacA(+) BCS can disrupt cytoskeletal architecture, likely through affecting the expression of cytoskeleton-associated genes, directly induce the expression of tumor promoter-related genes and inhibit the expression of tumor suppressor genes, thus favoring the development of tumors. VacA(+) BCS can also alter the expression of inflammation and stress response genes. This suggests that VacA may play an important role in the pathogenicity of H pylori.